Legalitas Advokat Dalam Perspektif Hukum Islam - Debi fazila; Syahrina Siregar; Fauziah lubis (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research a normative juridical approach because it uses secondary data as the main data source, which is also based on law No.18 of 2003 and sources of islamic law, namely the koran, hadith, and also the opinions of the scholars. There is also secondary legal material in the form of references to several books and also some existing journals. The rosults of this study are regarding how the legality of the perspective of islamic law advocates is that and islam there is no word advocate. But if we look at its function, jurists equate the position of an advocate in islam with a provider of legal aid services, sech as: hakam, mufti, mushalih. The theree legal aid providers are almost the same function as an advocate, namely law enforcement agencies outside the government whose job is to provide legal aidservices to the public. It is also said that before a case is submitted to the judicial process, the parties to the dispute are obliged to seek legal experts to give their ijtihad. So the legality of the advocate itself in islam also axists, it’s just that in islam thet don’t recognize the word advocate.